Gallium-68 prostate-specific membrane antigen PET-CT and the clinical management of prostate cancer. Issue 9 (September 2019) - Davidson, Tima; Amit, Uri; Saad, Akram; Hahiashvili, Maia; Goshen, Elinor; Portnoy, Orith; Berger, Raanan; Goldstein, Adam; Sadetsky, Igor; Weizman, Noam; Chikman, Bar; Dotan, Zohar; et al.
Abstract : Objectives: The purpose of this study was to evaluate the use of Gallium-68 prostatic-specific membrane antigen (PSMA) PET-computerized tomography (CT) in patients with prostate cancer undergoing imaging for initial staging, biochemical failure or the evaluation of metastatic disease. Methods: This is a single institution retrospective study of 95 patients with prostate cancer who were referred for PSMA PET-CT scans. The National Comprehensive Cancer Network guidelines were used to generate treatment recommendations. Univariate and multivariate statistical analyses were performed to identify parameters associated with positive findings on a PET-CT PSMA scan. Results: Mean age, Gleason score, and median prostate serum antigen (PSA) were: 72 years, 7.6 and 4 ng/ml, respectively. PSMA PET-CT was positive in 75.5% of the patients. A maximum standardized uptake value was 10.7 ± 8.8. PSMA avidity increased with rising PSA level: PSA ⩽ 1 ng/ml: 5/15 patients (33%); PSA 1–5 ng/ml: 18/27 patients (67%), and PSA ≥ 5 ng/ml: 33/34 patients (97%). Following imaging in nine high-risk patients referred for staging, changes in treatment occurred in 6 (67%). Treatment recommendations changed in 27/35 (65%) patients referred due to biochemical failure; these included recurrences suitable for salvage therapy ( n = 14), metastatic disease not suitable for salvage therapy ( n = 10), and no lesion ( n = 17). No changes in treatment occurred in any of the 35 patients referred to evaluate metastatic disease. Discussion: PSMA PET-CT imaging may have a substantial impact on clinical management in prostate cancer patients at the time of initial staging or with biochemical failure; yet this modality does not appear useful in the management of patients with known metastatic disease.